Avian Influenza A(H5N1) Virus Outbreak Investigation: Application of the FAO‐OIE‐WHO Four‐way Linking Framework in Indonesia. (22nd September 2014) - Setiawaty, V.; Dharmayanti, N. L. P. I.; Misriyah; Pawestri, H. A.; Azhar, M.; Tallis, G.; Schoonman, L.; Samaan, G.
Summary WHO, FAO and OIE developed a 'four‐way linking' framework to enhance the cross‐sectoral sharing of epidemiological and virological information in responding to zoonotic disease outbreaks. In Indonesia, outbreak response challenges include completeness of data shared between human and animal health authorities. The four‐way linking framework (human health laboratory/epidemiology and animal health laboratory/epidemiology) was applied in the investigation of the 193rd human case of avian influenza A(H5N1) virus infection. As recommended by the framework, outbreak investigation and risk assessment findings were shared. On 18 June 2013, a hospital in West Java Province reported a suspect H5N1 case in a 2‐year‐old male. The case was laboratory‐confirmed that evening, and the information was immediately shared with the Ministry of Agriculture. The human health epidemiology/laboratory team investigated the outbreak and conducted an initial risk assessment on 19 June. The likelihood of secondary cases was deemed low as none of the case contacts were sick. By 3 July, no secondary cases associated with the outbreak were identified. The animal health epidemiology/laboratory investigation was conducted on 19–25 June and found that a live bird market visited by the case was positive for H5N1 virus. Once both human and market virus isolates were sequenced, a second risk assessment was conducted jointly by the human health and animal health epidemiology/laboratory teams. This assessment concluded that the likelihood of additional human cases associated with this outbreak was low but that future sporadic human infections could not be ruled out because of challenges in controlling H5N1 virus contamination in markets. Findings from the outbreak investigation and risk assessments were shared with stakeholders at both Ministries. The four‐way linking framework clarified the type of data to be shared. Both human health and animal health teams made ample data available, and there was cooperation to achieve risk assessment objectives.